EDITORIAL - Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
Dear friends, These days our lives are run by COVID-19. Our gymnastic family mourns Dieter Hoffman, an excellent German coach and expert, a FIG Academy lecturer, who recently died of Covid-19. We do not know what comesnext but I am certain we all want to go back to our normal life. Despite many negative effects of Covid-19, it had a positive effect on our journal. Our authors wrote as many as16 articles for this issue which is a record for the journal. We are all adjusting to new circumstances. As you probably already know, conferences will be held online. Bulgaria will host a symposium on rhythmic gymnastics and Portugal on gymnastics. For more detailed information please see the following pages. Please join the symposia and take an active part with your ideas and views! For this issue our authors researched many different topics, including biomechanics, motor control, motor learning, theory of training, physiology, psychology, physical education, sociology and history, in relation to rhythmic and artistic gymnastics and trampolining. Countries participating with articles include: USA, Slovakia, Tunisia, Germany, Brazil, Australia, Portugal, Slovenia, Spain, Turkey, Greece, Iran and Ukraine. AntonGajdoš provides a short historical note on Nina Bocharova, the Olympic Champion from Russia in WAG at the Olympics 1952 in Helsinki. Our editorial board decided to make an exception and publish a letter -manifesto of International Socio-Cultural research group on WAG lead by Natalie Barker-Ruchti (USA)to the Editorand a comment on the letter by William Sands (USA). While we believe the letter and the comment present issues that may be important to our audiences, I'd like to stress that our journal remains focused on the publication of scientific articles presenting evidence-based solutions only. Nevertheless, there should be no doubt that our journal supports the United Nations Declaration of Human and Children Rights and believes its provisions should be respected. Just to remind you, if you quote the Journal,its abbreviation on the Web of Knowledge is SCI GYMN J. I wish you pleasant reading and a lot of inspiration for new research projects and articles, Ivan Čuk, Editor-in-Chief